Analisis Empiris Perkembangan Green Sukuk dan Alokasinya terhadap Infrastruktur Hijau di Indonesia - M Yasfin Nasution; Sugianto Sugianto; Muhammad Ikhsan Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the development of green sukuk and its allocation to green infrastructure in Indonesia during the 2018–2024 period. The approach used in this study is a descriptive approach with a literature study method (library research) using secondary data obtained from official reports of the Ministry of Finance of the Republic of Indonesia and other related publications. The analysis technique used is descriptive statistics through data presentation in the form of tables and graphs. The results of the study indicate that the development of green sukuk in Indonesia has experienced an upward trend although there are fluctuations in several periods. The allocation of green sukuk funds is spread across various green infrastructure sectors with dominance in the water management, sustainable transportation, and resilience to climate change sectors. In addition, green sukuk has been realized in various real projects, such as the development of transportation infrastructure, renewable energy, and environmentally friendly buildings that provide direct contributions to sustainable development. However, the results of the study also show an imbalance in the distribution of allocations between sectors, especially in the renewable energy and green building sectors which are still relatively low. Therefore, optimization is needed in the management and distribution of green sukuk funds to provide a more equitable and effective impact in supporting green infrastructure development in Indonesia.